Restritividade da legislação ambiental em postos de combustíveis - Franceschi, Franciéli Rosa de (2012)
This study sought to ascertain the environmental legislation applicable to the gas stations howmuch as the limitations of its provisions, noting the penalties associated to no compliance withthose laws. To this end, used the bibliographic search of exploratory qualitative, because it is asubject little explored. The new Resolution CONAMA provides penalties such as fines, bans andeven closure of establishments which do not adapt of her, and combined with the EnvironmentalCrimes Law, administrative sanctions are increase of penalties, who criminally responsible thosewho omit their environmental obligations. Entrepreneurs must be aware of the environmentalliabilities, which can affect not only the finance and the real estate value of the business, but alsoincur liability in any system of succession in spot of the contaminated area, thus, the effectiveenvironmental management is more than a legal compliance, is also a matter of business survival.